2023
DOI: 10.2147/ccid.s396272
|View full text |Cite
|
Sign up to set email alerts
|

New Mechanistic Insights of Melasma

Abstract: Melasma is a common acquired disorder of pigmentation that negatively impacts quality of life. Present treatments show poor therapeutic effect with frequent recurrence. This in large part is due to the currently limited understanding of the disease's etiology. It is urgent to elucidate the pathogenesis of melasma to further the discovery of new therapeutic strategies. Recent studies show that melasma is triggered or aggravated by a variety of factors, including genetic susceptibility, ultraviolet radiation, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
41
0
9

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 78 publications
0
41
0
9
Order By: Relevance
“…2 Melasma is categorised as epidermal, dermal, or mixed form based on the location of the pigment by Wood's lamp examination. 3 Even if the ultraviolet light exposition and hormonal influences seem to be the most influencing factors in the appearance of symptoms, the aetiology is probably multifactorial and not too clear. 4 Indeed, when compared to healthy volunteers, melasma patients have greater melanogenesis and higher markers of oxidative stress, suggesting that UV light both initiates and contributes to the condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Melasma is categorised as epidermal, dermal, or mixed form based on the location of the pigment by Wood's lamp examination. 3 Even if the ultraviolet light exposition and hormonal influences seem to be the most influencing factors in the appearance of symptoms, the aetiology is probably multifactorial and not too clear. 4 Indeed, when compared to healthy volunteers, melasma patients have greater melanogenesis and higher markers of oxidative stress, suggesting that UV light both initiates and contributes to the condition.…”
Section: Introductionmentioning
confidence: 99%
“…The centrofacial, malar and mandibular forms of melasma are the three most common 2 . Melasma is categorised as epidermal, dermal, or mixed form based on the location of the pigment by Wood's lamp examination 3 …”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the etiology of melasma is still unclear. Many factors may contribute to the development of the disease, including genetics, sunlight, endocrine stimulation, oxidative conditions, and morphofunctional changes 4 . Additionally, melasma has adverse psychological effects on numerous patients, such as anxiety disorders, depression, and somatoform disorders 5–9 …”
Section: Introductionmentioning
confidence: 99%
“…Many factors may contribute to the development of the disease, including genetics, sunlight, endocrine stimulation, oxidative conditions, and morphofunctional changes. 4 Additionally, melasma has adverse psychological effects on numerous patients, such as anxiety disorders, depression, and somatoform disorders. [5][6][7][8][9] Treatment options for melasma include systemic treatment, topical treatment, microneedling, peeling, light, and laser therapy.…”
mentioning
confidence: 99%
“…[1][2][3] Epidemiological studies have revealed significant variations in the prevalence of melasma across different populations: It is more common in Middle Eastern, East Asian, Mediterranean-African, and South American populations. 4,5 Based on recent data, in Germany, melasma is more common in individuals with intermediate skin phototypes (III, IV, and V), and the female-to-male ratio of melasma cases is approximately 5.12. 6 In Brazil, melasma is also more prevalent in woman (97.5%), preferentially with skin phototypes II, III, and IV.…”
Section: Introductionmentioning
confidence: 99%